The effect of different shading net on the Quantum Efficiency of PS II in chilli pepper cultivar ‘Star Flame’ - Agyemang Duah, Stella; Nagy, Zsuzsa; Helyes, Lajos (Acta Agraria Debreceniensis, 2019)
The study was undertaken to identify the effect of different shading net on the quantum efficiency of PS II on ‘Star Flame’ chilli pepper (Capsicum annuum) over a period of time cultivated under plastic house environment. ‘Star Flame’ pepper was grown under red shading net and samples without shading were used as control. Analysis of photosynthetic activity revealed a significant difference (p